2010
DOI: 10.1186/1471-2229-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Iron and ferritin accumulate in separate cellular locations in Phaseolus seeds

Abstract: BackgroundIron is an important micronutrient for all living organisms. Almost 25% of the world population is affected by iron deficiency, a leading cause of anemia. In plants, iron deficiency leads to chlorosis and reduced yield. Both animals and plants may suffer from iron deficiency when their diet or environment lacks bioavailable iron. A sustainable way to reduce iron malnutrition in humans is to develop staple crops with increased content of bioavailable iron. Knowledge of where and how iron accumulates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 50 publications
5
58
0
1
Order By: Relevance
“…Therefore, the highest accumulation of iron was found in the seed coats of Mesoamerican common bean seeds, which agrees with the results of Ariza-Nieto et al (2007), Cvitanich et al (2010), and Ribeiro et al (2012). The iron present in the seed coat of the common bean seeds was more bioavailable to the human body (Lombardi-Boccia et al, 1995).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, the highest accumulation of iron was found in the seed coats of Mesoamerican common bean seeds, which agrees with the results of Ariza-Nieto et al (2007), Cvitanich et al (2010), and Ribeiro et al (2012). The iron present in the seed coat of the common bean seeds was more bioavailable to the human body (Lombardi-Boccia et al, 1995).…”
Section: Resultssupporting
confidence: 89%
“…The distribution of iron between the embryo and the seed coat fractions of common bean seeds can vary among gene pools, as observed in the present study and by Ariza-Nieto et al (2007), Cvitanich et al (2010), Ribeiro et al (2012), and Blair et al (2013). Since iron is accumulated more in the embryo of the Andean Pesq.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Common bean and soybean genotypes were reported to accumulate different proportion of total seed Fe in the seed coat, embryo, and cotyledons (Laszlo 1990;Moraghan 2004;Ariza-Nieto et al 2007;Cvitanich et al 2010Cvitanich et al , 2011, indicating that specific tissues relevant for Fe storage should be identified and their Fe loading mechanisms be investigated to exploit such variability toward developing seed iron-dense cultivars. Using (-PIXE assay to investigate Fe distribution in seed tissues of Phaseolus species, Cvitanich et al (2010Cvitanich et al ( , 2011 concluded that (1) the distribution of Fe in seed depends on the species and genotype, (2) high concentrations of Fe accumulate in cells surrounding the provascular tissue, (3) the tissue in the proximity of the provascular bundles holds up to 500 mg g À1 Fe, depending on genotypes, and (4) the largest proportion of seed Fe in Phaseolus species is stored in compounds and cell parts different from ferritin and starch vacuoles. These results indicate that more studies are needed to assess the patterns of micronutrient distribution in seeds, and that micronutrient distribution criteria should be integrated into the selection strategies for biofortification of staple crops.…”
Section: B Distribution Of Iron and Zinc In The Seedmentioning
confidence: 99%